The Neumann Problem for a Class of Fully Nonlinear Elliptic Partial Differential Equations (Analysis in Theory and Applications, 2023)
In this paper, we establish global $C^2$ estimates to the Neumann problem fora class of fully nonlinear elliptic equations. As an application, we prove the existenceand uniqueness of $k$-admissible solutions to the Neumann problems.